Effects of Xiangsha Liujunzi decoction drug serum on gastric antrum smooth muscle cells from rats with functional dyspepsia by regulating gastrointestinal hormones - Ning Dai; Jinghong Hu; Yan Liu; Dongyu Ge; Ruijuan Dong; Fengzhi Wu; Jiaojiao Yu; Mindan Chen; Deborah C. Ma; Feng Li (Journal of Traditional Chinese Medical Sciences, 2020)
Objective: To observe the effect and mechanism of Xiangsha Liujunzi decoction (XSLJZD) drug serum on gastric antrum smooth muscle cells (SMCs) in rats with functional dyspepsia (FD). Methods: Gastric antrum SMCs from rats with FD were isolated, cultured, and then divided into six groups as follows: control, model, domperidone, low-dose XSLJZD (LXSLJZD), medium-dose XSLJZD (MXSLJZD), and high-dose XSLJZD (HXSLJZD). Each group was administered the corresponding drug serum for intervention. Drug serum intervention conditions and proliferative activity of SMCs were tested by cholecystokinin octapeptide. Ghrelin, gastrin, somatostatin, and substance P (SP) levels were measured by ELISA. Somatostatin and SP mRNA expression was measured by real-time PCR. Results: A concentration of 10% drug serum for 24 h was decided to be the best intervention condition for later study. The mean optical density value in the model group was lower than that in the control group (P = .001). Optical density values in the domperidone and HXSLJZD groups were higher than those in the model group (P = .025, P = .032, respectively). Gastrin, SP, and ghrelin levels in the model group were lower (P = .007, P = .037, P = .005, respectively), but somatostatin levels were higher, compared with those in the control group (P = .031). Gastrin, SP, and ghrelin levels in the domperidone, MXSLJZD, and HXSLJZD groups were higher than those in the model group (all P<.05). Somatostatin levels in the four drug-treated groups were lower than those in the model group (P = .002, P = .007, P = .001, P = .009, respectively). SP mRNA levels in the model group were lower than those in the control, domperidone, MXSLJZD, and HXSLJZD groups (P = .037 P = .016, P = .025, P = .002, respectively). Somatostatin mRNA levels in the model group were higher than those in the control and MXSLJZD groups (P = .042, P = .035). Conclusions: XSLJZD and domperidone drug serum effectively promote proliferative activity of gastric antrum SMCs in an FD model. The mechanism of this activity may be regulated by gastrointestinal hormones. Keywords: Functional dyspepsia, Xiangsha Liujunzi decoction, Gastrointestinal hormones, Gastric antrum, Smooth muscle cells